2006
DOI: 10.1007/s00464-005-0391-3
|View full text |Cite|
|
Sign up to set email alerts
|

Fibrin glue for securing the mesh in laparoscopic totally extraperitoneal inguinal hernia repair

Abstract: Fibrin glue seems to be a reasonable, feasible, and maybe even competitive alternative to the standard tissue-penetrating mesh fixation. The results of this study justify launching larger trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…Second, several studies have demonstrated the safety (recurrence rate) of nonfixation of mesh in laparoscopic total extraperitoneal repair. Studies with a large number of patients with a long follow-up period 3 and meta-analysis 4 have confirmed this. What could be the possible explanation for this?…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Second, several studies have demonstrated the safety (recurrence rate) of nonfixation of mesh in laparoscopic total extraperitoneal repair. Studies with a large number of patients with a long follow-up period 3 and meta-analysis 4 have confirmed this. What could be the possible explanation for this?…”
supporting
confidence: 51%
“…3 Since 2003, I routinely glue the mesh in the majority of my laparoscopic groin and ventral/incisional hernia operations, sometimes in combination with sutures and/or tacks.…”
mentioning
confidence: 99%
“…In a meta-analysis by Sajid et al, the authors reported that the incidence of chronic groin pain is significantly reduced after light-weight implantation [35]. Moreover, several studies reported that the risk of acute and chronic pain after stapled mesh fixation is higher compared with fibrin fixation or non-fixation [36,37]. These studies add more evidence in favors of the anatomical configuration of Parietex® anatomical mesh which doesn't need fixation.…”
Section: Discussionmentioning
confidence: 77%
“…These authors were able to show that fi xation with fi brin sealant is mechanically equivalent to stapler fi xation. In a number of clinical studies, both its effi ciency and also a reduction in postoperative complication have been shown in inguinal hernia repair [20,21]. The use of fi brin sealant is now also being described for hiatus hernia repair.…”
Section: Discussionmentioning
confidence: 99%